INTERACTION OF UIN AR-RANIRY BANDA ACEH STUDENTS IN IMPROVING LEARNING MOTIVATION THROUGH THE USE OF PEER LESSONS STRATEGIES - Usman Usman (STAI Al-Washliyah Banda Aceh, 2020)
This paper discusses that learning is not just, writing and memorizing, but students can exchange ideas in learning so that students will establish relationships with others, by teaching material to classmates, learning from friends, to create student motivation The problem in this paper is, whether student interaction can increase learning motivation using the Peer Lessons strategy (Learning from Friends)? The purpose of this study is to find out to determine student interactions in increasing motivation to use the Peer Lesson learning strategy (Learning from Friends). To answer this problem, this study uses a qualitative approach with the number of 2 lecturers, 5 students of Ar-Raniry UIN Banda Aceh. Data collection is done using observation techniques, and interviews. The results of this study indicate that the use of the Peer Lessons strategy (Learning from friends) students can easily exchange ideas with friends about learning that is difficult to understand, both groupmates or not to increase motivation in learning, therefore, with friends, Students can form study groups, so they can exchange ideas to solve problems, such as college assignments or discuss learning difficulties, study together to face exams or motivate one another in terms of learning